Artificial intelligence as a determinant for reshaping the automotive industry and urban mobility services. (28th July 2022) - Antonialli, Fabio; Martinesco, Andrea; Mira-Bonnardel, Sylvie
With the growing interest in smart cities and autonomous mobility, policymakers, citizens, and the automotive industry face a looming shift towards intelligent mobility solutions. By filling a gap of transversal analysis among artificial intelligence (AI), the automotive industry, and urban mobility; the present study discusses how AI has been transforming both the automotive industry and urban mobility globally. By applying a qualitative and descriptive approach, data were collected from primary and secondary sources and analysed from the standpoint of technology, regulations (public policies), and citizens (users). The results show how AI is bringing the traditional automotive industry and the urban mobility sector closer through mobility-as-a-service schemes and illustrate with the city of Curitiba (Brazil) how such AI-enabled technological advances linked with public policies can help design sustainable urban mobility in developing countries.